Impact of Monitoring Mechanisms on Environmental Disclosure Quality in Nigeria - Saheed Olanrewaju Issa; Nasiru Yunusa; Aisha Mahmoud Hamman (Indonesian Journal of Sustainability Accounting and Management, 2021)
Environmental information can be a key element of corporate disclosure. It can alarm stakeholders due to various problems as well as low data quality and infrequent reporting, in Nigeria. In order to address these problems, this study examines the impact of monitoring mechanisms on environmental disclosure quality in Nigeria. The data in this study is drawn from annual reports and content analysis of 46 listed environmentally sensitive firms over seven years (2012–2018) obtained from the Nigerian Stock Exchange. The authors analyzed the data using panel corrected standard error (PCSE) regression analysis. The findings show a significant positive correlation between board independence, the presence of an environmental committee, environmental audit, and environmental disclosure quality. However, institutional ownership has an insignificant relationship to environmental disclosure quality. In conclusion, the overall results reinforce the study's general argument of monitoring the how companies respond to the needs and interests of various stakeholder groups and consequently, determining the quality of environmental disclosures made by those same companies. Based on the results that show lower rates of environmental reporting, this study provides a way forward for the government and policy makers to address environmental issues in Nigeria.